Eksistensi Hukum Adat Mosehe Masyarakat Tolaki pada Penyelesaian Perkawinan di Desa Woiha, Kolaka Timur - Yeni Haerani; La Ode Dedihasriadi; Patmasari Patmasari; Edy Nurcahyo (Lembaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2023)
Mosehe is a symbol or symbol that expresses the conception of the Tolaki tribe, both to humans, the universe and the relationship between humans and other humans. Mosehe is divided into two, namely Mosehemohewu and Moseheowose or Mosehewonua. Mosehemohewu is held in a simple form, namely if there is conflict between humans, both individuals within the family, and between families. The author's focus is Mosehe in the simple form of conflict between individual humans in the family (marital problems). The research method used is empirical legal research. The data used is data that is directly obtained from data sources in the field (field research) and then described. The existence and role of Mosehe in solving problems in marriage in Woiha Village, Tirawuta District, East Kolaka Regency is very important, where the Mosehe ceremony is not only a sacred activity but is also believed to reject all dangers or repel reinforcements. Plays an important role in solving various problems in marital problems, such as elopement, pregnancy out of wedlock and other marital problems, because in the symbol of the mosehe ceremony it is symbolized as an act of purification from all sins/mistakes.